2009
DOI: 10.1111/j.1365-3040.2009.01971.x
|View full text |Cite
|
Sign up to set email alerts
|

The plasma membrane Na+/H+ antiporter SOS1 is essential for salt tolerance in tomato and affects the partitioning of Na+ between plant organs

Abstract: We have identified a plasma membrane Na + /H + antiporter gene from tomato (Solanum lycopersicum), SlSOS1, and used heterologous expression in yeast to confirm that SlSOS1 was the functional homolog of AtSOS1. Using posttranscriptional gene silencing, we evaluated the role played by SlSOS1 in long-distance Na + transport and salt tolerance of tomato. Tomato was used because of its anatomical structure, more complex than that of Arabidopsis, and its agricultural significance. Transgenic tomato plants with reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
253
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 327 publications
(267 citation statements)
references
References 66 publications
11
253
0
3
Order By: Relevance
“…Also, Arabidopsis nhx1 mutant plants had reduced leaf area and smaller epidermal cells (Apse et al, 2003), suggesting that these mutant plants do not supply the vacuoles with sufficient osmotic potential for the normal expansion of leaf cells, which largely depends on K + accumulation (Maggio et al, 2006). Under salt stress, K + concentrations in different parts of tomato plants decreased, whereas the Na + concentration increased in both transgenic and control lines, following well-known patterns of salt-related mineral changes in tomato (Rush and Epstein, 1981;Olias et al, 2009). However, no consistent differences in Na + contents among transgenic and control lines were observed after saline treatments (Tables 1 and S1), despite the significant enhancement of Na + /H + antiporter activity in tonoplast vesicles purified from these transgenic plants (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Arabidopsis nhx1 mutant plants had reduced leaf area and smaller epidermal cells (Apse et al, 2003), suggesting that these mutant plants do not supply the vacuoles with sufficient osmotic potential for the normal expansion of leaf cells, which largely depends on K + accumulation (Maggio et al, 2006). Under salt stress, K + concentrations in different parts of tomato plants decreased, whereas the Na + concentration increased in both transgenic and control lines, following well-known patterns of salt-related mineral changes in tomato (Rush and Epstein, 1981;Olias et al, 2009). However, no consistent differences in Na + contents among transgenic and control lines were observed after saline treatments (Tables 1 and S1), despite the significant enhancement of Na + /H + antiporter activity in tonoplast vesicles purified from these transgenic plants (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms operate mainly through extrusion, exclusion or compartmentation of excess Na (Munns 2002), involving various specific transporters. For example, they include the retrieval of Na from the xylem by the AtHKT1 transporter (Sunarpi et al 2005;Hausser and Horie 2010), Na exclusion through absorption from the transpiration stream by the HKT1;1 transporter in root stele (Møller et al 2009), Na extrusion out of root cells by SOS1 antiporter (Olias et al 2009) and vacuolar sequestration mediated by the vacuolar Na + /H + antiporter (Tester and Davenport 2003). The higher Na accumulation in stem and root and reduced leaf accumulation in huckleberry indicate the presence of a Na transport regulatory mechanism at the level of the stem, similar to the results of Olias et al (2009).…”
Section: Mineral Accumulationmentioning
confidence: 99%
“…Studies with Arabidopsis thaliana showed that SOS1 is not essential to plant growth and normal development, but is critical to the development of tolerance to salt (Wu et al 1996, Shi et al 2002. In studies with tomato Olías et al (2009) showed that SOS1 gene silencing resulted in negative effects on plant growth under salt stress. It was shown that, besides its main action in the extrusion of Na + out of the root tissue, SOS1 is critical for the partitioning of Na + in plant organs, besides participating in the retention of Na + in stems of tomato, to prevent it from reaching photosynthetic tissues.…”
mentioning
confidence: 99%